2020
DOI: 10.1002/masy.201900209
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Synthesis of CuS Thin Film for Supercapacitor Application

Abstract: In present research, walnut like copper sulfide is prepared via a facile single‐step potentiostatic electrodeposition method on conducting stainless steel substrate. The walnut like morphology of copper sulfide thin film lies of microplates and further microplates converted to nanogranuals, by means of a change in deposition time and thickness. Copper sulfide thin film electrode reveals a specific capacitance of 132 F g−1 at 50 mA cm−2. The film thickness changes with deposition time. The films acquire maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In addition, the effects of various parameters controlling the electrochemical properties and morphology of the chalcogenides synthesized via the electrodeposition method were addressed. The table shows the potential activity of electrodeposited TMCs as compared to other electrode materials [75–97] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In addition, the effects of various parameters controlling the electrochemical properties and morphology of the chalcogenides synthesized via the electrodeposition method were addressed. The table shows the potential activity of electrodeposited TMCs as compared to other electrode materials [75–97] …”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Such strategies include using a binder-free film deposition technique such as electrochemical deposition and forming a composite with carbon-based materials, notably graphene. Besides its simplicity, the electrochemical deposition method allows for binder-free, direct binding of the electroactive material on the conductive substrate enhancing the effective contact area between active materials and electrolytes, and the substrate thereby effectively reducing the impedance of the electrode for ion and electron transport (charge transfer) leading to the much improved electrochemical performance. The performance of the pristine Cu 4 SnS 4 materials can also be enhanced by the formation of a composite with graphene. Studies have shown that incorporating reduced graphene oxide (rGO) with transition-metal sulfides has been shown to enhance their capacitive performance by a factor of more than ∼1.5 × (see Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers described that several deposition methods achieved the requirements of highly oriented thin film growth. These deposition methods such as aerosol assisted chemical vapour deposition [4], SILAR method, pulsed laser deposition [5], solvo thermal technique [6], electron beam evaporation technique [7], molecular beam epitaxy method [8], radio frequency sputtering technique [9], chemical bath deposition method [10][11][12], atomic layer deposition technique [13], spray pyrolysis method [14], and electro deposition method [15][16][17]. The obtained films could be employed in several applications including opto-electronic [18,19], solid state and medical devices [20].…”
Section: Introductionmentioning
confidence: 99%